2016
DOI: 10.1590/s0004-28032016000300008
|View full text |Cite
|
Sign up to set email alerts
|

NEOADJUVANT THERAPY AND SURGERY FOR RECTAL CANCER. Comparative study between partial and complete pathological response

Abstract: -Background -The approach of locally advanced extra-peritoneal rectal adenocarcinoma implies a treatment with neoadjuvant chemoradiotherapy associated with total mesorectal excision surgery. However, the tumors respond variably to this neoadjuvant therapy, and the mechanisms for response are not completely understood. Objective -Evaluate the variables related to the complete tumor response and the outcomes of patients who underwent surgery, comparing those with partial tumor regression and those with total rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Surgical resection is the cornerstone of curative management, with total mesorectal excision (TME) plays a fundamental role in patients who undergo rectal surgery [2][3][4]. With advancement in oncological therapies, neoadjuvant therapy prior to surgical resection of rectal cancer increased overall survival, disease-free survival, and reduced local recurrence rate [5,6]. Therefore, neoadjuvant therapy is now the gold standard of treatment for locally advanced mid and low rectal cancer before subjecting patients to curative surgery resection (with criteria of T3 and above, positive mesorectal nodes, mesorectal fascia involvement or when mesorectal fascia is threatened) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical resection is the cornerstone of curative management, with total mesorectal excision (TME) plays a fundamental role in patients who undergo rectal surgery [2][3][4]. With advancement in oncological therapies, neoadjuvant therapy prior to surgical resection of rectal cancer increased overall survival, disease-free survival, and reduced local recurrence rate [5,6]. Therefore, neoadjuvant therapy is now the gold standard of treatment for locally advanced mid and low rectal cancer before subjecting patients to curative surgery resection (with criteria of T3 and above, positive mesorectal nodes, mesorectal fascia involvement or when mesorectal fascia is threatened) [7].…”
Section: Introductionmentioning
confidence: 99%
“…The factors are size, grading and differentiation of tumor, tumor distance from the anal verge, serum CEA and fibrinogen level, blood cell counts, gap between neo-CRT and surgery, and many other proposed factors. 5 , 9 , 11 , 13 - 19 , 21 , 23 , 28 - 29 , 35 - 41 Also, some factors including involvement of lymph nodes at the beginning of disease, unfavorable tissue presentations like lymphovascular and perineural invasion, and high-grade tumors have been proposed to be associated with lymphatic system involvement even despite the achievement of cPR. 42 Even so, there is still no agreement on any of the above-mentioned factors regarding predictor factors of cPR and wait and watch policy in the treatment of rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 9 , 10 , 14 , 23 , 33 , 34 In recent years, many studies have tried to find the predicting factors of cPR following neo-CRT in rectal cancer. 5 , 9 , 11 , 13 - 19 , 21 , 23 , 28 , 29 , 35 - 42 Even so, there is still no agreement on any of the proposed factors regarding predictors of cPR and “wait and watch policy” in the treatment of rectal cancer. 3 , 12 , 15 , 17 , 19 , 20 , 28 , 31 , 33 , 38 , 43 - 45 Therefore, considering its importance, it is still a hot topic of research in rectal cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that as the interval time increased within 12 weeks, the rate of tumor regression and pCR rate increased gradually, which would decrease over 12 weeks interval time. 14 De Andrade et al 41 performed a study which exhibited that interval time was the sole influencing factor of pathological complete remission, and prolonging interval time over 8 weeks would clearly increase the pathological complete remission rate. However, some other studies have shown that prolonging the interval time after nCRT did not increase pCR; instead, this would increase postoperative complications and the occurrence of distant metastasis during the waiting period.…”
Section: Discussionmentioning
confidence: 99%